(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
Recombinant protein expression in E. coli remains one of the most common and cost-effective methods for producing target proteins for scientific and biotechnological purposes. The success of this process is largely determined by the optimisation of cultivation conditions, including inoculation parameters, the presence of selective agents, and the expression induction regime. This study investigates the influence of key factors on the expression of the recombinant SM protein of SARS-CoV-2 in E. coli. The main focus was on inoculum dilution, the presence of ampicillin in the culture medium, and the concentration of IPTG inducers during incubation at 37 °C 4 hours before induction and 4 hours after. The results showed that an optimal inoculum dilution of 1:100 provides maximum protein yield with balanced culture growth. The presence of ampicillin ensures stable plasmid retention and maintenance of plasmid-carrying cell cultures, which has a positive effect on productivity. The use of IPTG at a concentration of 0.5 mM enables a high level of expression to be achieved without a significant reduction in growth. The selected conditions increase the efficiency of recombinant SM protein production and can be applied in process scale-up.